Priznanje in izvršitev tujih sodnih odločb v Republiki Sloveniji - Wedam-Lukić, Dragica (Pravni letopis, 2011)
The author describes the recognition and enforcement of foreign judgements in the Republic of Slovenia under the Act on Private International Law and Procedure which applies to decisions deriving from the states which are not members of the EU, and under "European law" which applies to decisions deriving from other member state. Under Slovenian law the court of enforcementcan decide whether a foreign judgement fulfils the requirements for the execution as a preliminary question, while according to the Brussels' Regulations a judgement given in one member state in order to be enforced in another member state, has first to be declared enforceable in a special intermediate procedure by a competent court of the state of enforcement. Under some subsequent regulations concerning particular matters the declaration of enforceability is no longer necessary. The abolition of the exequatur procedure (with some safeguards) is also one of the aims of the proposed modification of the Regulation Brussels I. Consequently, a question arises how to connect these new solutions with notions of our enforcement law. The author opines that the amendments of the domestic law would be necessary to provide legislative solutions for the implementation of said regulations.
Keywords: Act on Private International Law and Procedure; bruseljske uredbe; Brussels' Regulations; Community law; eksekvatura; exequatur; foreign judgements; izvršba; izvršilni postopek; mednarodna sodišča; odločbe; pravo Evropske skupnosti; priznanje in izvršitev; recognition and enforcement; sodišča; tuje sodne odločbe; Uredba Bruselj I; Zakon o mednarodnem zasebnem pravu in postopku